Serum apolipoprotein C-III in high-density lipoprotein: a key diabetogenic risk factor in Turks - Onat, A.; Hergenc, G.; Ayhan, E.; Ugur, M.; Kaya, H.; Tuncer, M.; Can, G. (WILEY, 2009)
Aims We studied determinants of serum apolipoprotein C-III (apoC-III) and whether levels of apoC-III or its fractions predict metabolic syndrome (MetS), Type 2 diabetes and coronary heart disease (CHD). Methods The predictive value of apoC-III, measured by immunoturbimetric immunoassay in 802 tracked individuals of a Turkish general population in determining cardiometabolic risk was assessed over 4.4 +/- 1.2 years' follow-up. Patients with MetS, Type 2 diabetes and CHD at baseline were excluded. Results Total apoC-III, as well as both fractions, was significantly, linearly and inversely related to smoking status, positively to alcohol usage and to levels of complement C3. Mid and high tertiles of total or non-high density lipoprotein (HDL) apoC-III predicted significantly and independently incident MetS; they predicted CHD with risk ratios of 1.6 [95% confidence intervals (CI) 1.02-2.5], for 1 sd increment, after adjustments that included HDL cholesterol and body mass index (BMI). The highest tertile of HDL apoC-III was a major independent predictor of new-onset diabetes with a 2.5-fold risk ratio for 1 sd increment (95% CI 1.5-4.0) in combined sexes, after adjustment for waist circumference, HDL cholesterol and other confounders and was a better predictor than waist girth. Conclusions Serum total apoC-III or its fractions are linearly and inversely associated with smoking, positively with alcohol usage and serum complement C3. The presumably dysfunctional HDL apoC-III is a stronger predictor of Type 2 diabetes than waist girth in Turks. Non-HDL apoC-III predicts strongly the development of MetS as well as incident CHD, independent of HDL cholesterol, BMI and non-lipid factors. The atherogenicity of apoC-III and dysfunctionality of HDL apoC-III carry huge public health implications in Turks.
Keywords: apolipoprotein C-III; cigarette smoking; coronary heart disease; diabetes Type 2; high-density lipoprotein; METABOLIC SYNDROME; CORONARY RISK; DISEASE; CIII; DYSLIPIDEMIA; ASSOCIATION; DEFINITION; OBESITY; PLASMA; LIPASE; Endocrinology & Metabolism